2007 IEEE International Electron Devices Meeting 2007
DOI: 10.1109/iedm.2007.4418875
|View full text |Cite
|
Sign up to set email alerts
|

On the experimental determination of channel back-scattering in nanoMOSFETs

Abstract: By using accurate Multi-Subband-Monte-Carlo simulations of quasi-ballistic transport we carry out a detailed re-examination of the experimental extraction procedure for the ballistic-ratio BR=I D /I BAL in nanoMOSFETs proposed in [1]. It is found that the ballistic-ratio extracted applying this procedure to the simulated drain current severely underestimates the BR extracted by directly compare the simulated I D and I BAL . This is mainly due to inaccurate determination of the temperature dependence of the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 8 publications
2
8
1
1
Order By: Relevance
“…This dependency has been confirmed by Monte Carlo simulations 38 . Note that this apparent mobility corresponds to the mobility extracted from experiments, using the usual Drift Diffusion formula.…”
Section: Lundstrom Models Of Backscatteringsupporting
confidence: 62%
“…This dependency has been confirmed by Monte Carlo simulations 38 . Note that this apparent mobility corresponds to the mobility extracted from experiments, using the usual Drift Diffusion formula.…”
Section: Lundstrom Models Of Backscatteringsupporting
confidence: 62%
“…We want to point out that the most recent papers [11][12][13][14][15] use the Chen method to extract the backscattering coefficient and that the obtained results can be biased according to our previous considerations. Moreover, Zilli [17] attributed to A1 the major impact on the extracted backscattering, while here we found that is A5 the poorer approximation.…”
Section: Germanium P-mosfetsmentioning
confidence: 47%
“…For example, one of the most widely used techniques is the one that is based on the temperature dependence of I SAT to extract the ratio of the mean free path to the critical length of the KT layer, hence BR [25]. However, it turned out to be quite controversial, as discussed in [24] and [26]. On the other side, being experimental does not guarantee the absolute validity of the extracted values, since the whole problem lies in the extraction of I BAL value, which remains a theoretical term.…”
Section: Ballisticity Ratio: How Closementioning
confidence: 99%